SPORES GERMINATION OF Dicksonia sellowiana AND INITIAL GROWTH UNDER DIFFERENT LEVELS OF IRRADIANCE - BIASI, Luiz Antonio; do VALLE, Fátima Cristina (Scientia Agraria, 2009)
Dicksonia sellowiana is an endangered native tree fern of Brazil because the trunks have been indiscriminately exploited. The aim of the present study was to obtain some information about the spores germination under control conditions and evaluated the effect of shadow on initial plant growth in the field. Different substrates were tested: sphagnum, “xaxim”, Plantmax HT®, phenolic foam, vermiculite, coconut fibre and brick peaces in greenhouse and growth room. Spores were placed on the wet substrates inside close and transparent boxes. In greenhouse, the sphagnum and “xaxim” showed best spore germination and in growth room, Plantmax HT® showed the highest gametophyte colonization. Spores germination was promoted by shadow. To evaluated the effect of shadow on initial plant growth in the field, the gametophytes formed in vitro were transferred to greenhouse, where formed the sporophytes. The plants were transferred to 53 cm3 tubs and when they showed 5 cm of height, they were transplanted to field under 100%, 50%, 20% and 10% of irradiance. Plants cultivated in the field under 100% of irradiance showed high deadly (40%) at 70 days and after 367 days anyone plant survive. The growth was higher for plants kept under only 20 and 10% of irradiance. It was concluded that the spores germination can be maid on boxes containing Plantmax HT® substrate covered with closed and transparent plastic bags with shadow. Plants of “xaxim” can’t be planted in the field under full irradiance, it is recommended shadow higher than 80%